Illumination of Hanjuang Flower Patterns in Mushaf Qur’an Sundawi - Agus Malik Ibrahim; Rahma Wahdiniwaty (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This research is motivated by the illumination of the Hanjuang floral motif in the Sundawi Qur’anic manuscript. Meanwhile, in general, manuscripts that are often circulated in good print from middle eastern Indonesia use illumination with a geometric Islamic pattern. The purpose of this study is to explain the Sundawi Qur’an as a whole related to the formulation of the Hanjuang floral motif illumination concept, an explanation of the Hanjuang floral motif illumination, and the relevance of the Hanjuang floral motif illumination to the Sundawi Qur’anic Mushaf. This study uses a qualitative method with an aesthetic approach that systematically describes the things that are the focus of the research. The data collection technique used in this research is library research and field research using the interview method with informants. The results of this study found that the formulation of the concept of illumination of the Hanjuang floral motif with the Sundawi Qur’anic Mushaf is one of the characteristics of West Java plants or flora and also as a means of introducing West Javanese ornaments in Sundawi Qur’anic manuscripts, this illumination will have an impact on the synergy between the decorative motifs and the writings on the Sundawi Qur’anic manuscripts verse and the Hanjuang motifs affect the reader’s enthusiasm to continue reading the Qur’an